The autonomic effects of deep brain stimulation-a therapeutic opportunity - Hyam, J; Kringelbach, M; Silburn, P; Aziz, T; Green, A (2012)
Deep brain stimulation (DBS) is an expanding field in neurosurgery and has already provided important insights into the fundamental mechanisms underlying brain function. One of the most exciting emerging applications of DBS is modulation of blood pressure, respiration and micturition through its effects on the autonomic nervous system. DBS stimulation at various sites in the central autonomic network produces rapid changes in the functioning of specific organs and physiological systems that are distinct from its therapeutic effects on central nervous motor and sensory systems. For example, DBS modulates several parameters of cardiovascular function, including heart rate, blood pressure, heart rate variability, baroreceptor sensitivity and blood pressure variability. The beneficial effects of DBS also extend to improvements in lung function. This article includes an overview of the anatomy of the central autonomic network, which consists of autonomic nervous system components in the cortex, diencephalon and brainstem that project to the spinal cord or cranial nerves. The effects of DBS on physiological functioning (particularly of the cardiovascular and respiratory systems) are discussed, and the potential for these findings to be translated into therapies for patients with autonomic diseases is examined. © 2012 Macmillan Publishers Limited.